Effectiveness of ZEP Quiz-Based Educational Games in Enhancing Students’ Motivation to Learn Arabic - Abdullah Syarofi; Abdul Mujib Murtadho; Khulafaur Rosyidin (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to examine the effectiveness of ZEP Quiz-based educational games in enhancing Arabic language learning motivation among students of SMK NU 2 Glagah, Lamongan. The declining motivation to learn Arabic in vocational Islamic secondary schools, attributed primarily to the monotonous nature of conventional instructional approaches, necessitates innovative pedagogical interventions. This study employed a quantitative approach with a one-group pretest-posttest quasi-experimental design. Data were collected from 27 twelfth-grade students using a pre-test on Arabic language proficiency and a 20-item Likert-scale motivation questionnaire. Data analysis involved descriptive statistics, the Shapiro-Wilk normality test, Paired Sample t-Test, Wilcoxon Signed Rank Test, and N-Gain analysis. The findings revealed a significant increase in learning motivation: the mean pretest score of 41.85 (low category) improved to a mean posttest score of 91.56 (very high category). The Paired Sample t-Test yielded t = 41.820 with p = 0.000 < 0.05, and the Wilcoxon test confirmed this result with Z = −4.541 and p = 0.000. The N-Gain score of 0.8618 falls within the high category, and Cohen’s d = 8.048 indicates a huge effect size. The novelty of this study lies in its specific examination of ZEP Quiz a gamification-based digital quiz platform as a motivational intervention in Arabic language learning at the vocational secondary school level. These findings provide empirical evidence that ZEP Quiz constitutes a highly effective educational media for improving student motivation in Arabic language instruction.